Student's Mathematical Connection to Problem-Solving Based on Rational Personality Types - Alkans Sofyawati Sutrisno; Toto Nusantara; Susiswo Susiswo (Jurnal Pendidikan Sains, 2019)
Abstract: The purpose of this study is to describe students’ mathematical connection of rational type students in solving mathematics problem. The research data was obtained by analyzing the answer sheets and interview of two subjects based on mathematical connection indicators. The results show the process of mathematical connection in everyday life that students do with rational personality type is complete. However, different results are found that in the connection between mathematical concepts and mathematical process connection processes as the equivalent representation of students with rational personality types is not yet complete.Key Words: mathematical connection, rational personality typesAbstrak: Tujuan penelitian ini untuk mendeskripsikan koneksi matematis siswa bertipe kepribadian rasional dalam memecahkan masalah Matematika. Penelitian ini merupakan penelitian deskriptif-kualitatif. Data diperoleh dari lembar jawaban dan wawancara terhadap dua subjek kemudian dianalisis berdasarkan indikator koneksi matematis. Hasil penelitian menyimpulkan bahwa subjek menunjukkan koneksi Matematika dalam kehidupan sehari-hari secara lengkap. Namun hasil berbeda ditemukan bahwa proses koneksi antar konsep Matematika dan proses koneksi prosedur Matematika sebagai representasi yang ekivalen dari siswa dengan tipe kepribadian rasional adalah belum lengkap.Kata kunci: koneksi matematis, tipe kepribadian rasional